Evaluation of Risks and Their Impact on Legal Validity in the Implementation of Electronic Notary Deeds in Indonesia - Nuriska, Citra; Sri Darmadi, Nanang (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to analyze: 1). The risks that arise in the implementation of electronic notarial deeds in Indonesia. 2) The impact of these risks on the legal validity of electronic notarial deeds according to the provisions of the applicable laws and regulations in Indonesia. This type of research is normative legal research. The approach method in this study is a statute approach and a conceptual approach. The type of data in this study is secondary data sourced from primary, secondary and tertiary legal materials. The data collection method uses literature studies. The analysis in this study is prescriptive. The results of the study concluded: 1). The implementation of electronic notarial deeds in Indonesia, based on Article 15 paragraph (3) of Law Number 2 of 2014 concerning the Position of Notary, faces cybersecurity risks (hacking, wiretapping, data loss), legal (unclear regulations, non-compliance with the principle of onmiddellijkheid), technical-operational (lack of notary competence, unstable infrastructure) and socio-ethical (misuse of electronic signatures). This risk violates Article 26 and 31 of the ITE Law, Article 16 paragraph (1) letter m of the Notary Law, Article 1867 and 1868 of the Civil Code, and Article 46 and 59 paragraph (3) of the PP PSTE, thus threatening the validity of deeds as authentic evidence and public trust. Solutions include regulatory harmonization, implementation of encryption and blockchain, Notary training, infrastructure investment and electronic signature certification to ensure legal certainty in accordance with Article 28 D paragraph (1) of the 1945 Constitution. 2). Cybersecurity risks (hacking, wiretapping, data loss), legal (unclear regulations, non-compliance with the principle of onmiddellijkheid), technical-operational (lack of Notary competence, unstable infrastructure) and socio-ethical (misuse of electronic signatures) threaten the validity of electronic Notary deeds. This risk violates Article 26 and 31 of the ITE Law, Article 16 paragraph (1) letter m of the Notary Law, Articles 1867, 1868 and 1869 of the Civil Code, and Articles 46 and 59 paragraph (3) of the PP PSTE, causing the deed to be at risk of losing its authentic status and not being recognized in court. The inconsistency of subordinate norms with the grundnorm of Article 28D paragraph (1) of the 1945 Constitution creates a hierarchical contradiction. Harmonization of regulations, cybersecurity, notary training, infrastructure investment and electronic signature certification are needed so that electronic deeds are equivalent to authentic deeds.